The local identity of Tian Si's Mahua ecological literary - Seng, Y.C. (2017)
The early stage, Mahua literature was influenced by China in terms of values and concepts. In addition, the western literature thought and the translation of literature also make Mahua literature influenced by western literature culture. With the transformation of the times, Mahua literature has gradually been transformed. by Malaysian cultural traditions. The poems of Tian Si can be considered as the pioneer of ecological poems and the works show his concern about the crisis in natural and in mental ecology under the powerful influence of commercialism in Sarawak. This paper emphasizeson the local identity of a series of ecological environment on his works from different styles of expression, a more comprehensive picture of deforestation, species crisis, soil erosion, miscellaneous pollution, smoke and haze disaster, mangroves atrophy, apes and threaten the survival of marine life, insects ravaged ecological crisis and environmental problems. The nature writing poems expresstheir ecological aesthetic appeal for the respect of life and, ecological ideal of returning to nature, in hopes of arousing people's aspiration for a harmonious nature.